Data Mining Applications for Violence Pattern Analysis with FP-Growth Algorithm - Junta Zeniarja; Debrina Luna Arghata Mangkawa; Abu Salam (Universitas Dian Nuswantoro and IndoCEISS, 2021)
Violence is a crime that is one of the problems the principal experienced by each country. Violence can be interpreted as a behavior that causes harm to someone. According to the results of DP3AKB research in Central Java Province in 2017, there are less many than 200 people in Central Java province experienced acts of violence. By because of the many acts of violence that occur in various forms of violence, it requires definite information about the form of violence that happens most often, in obtaining that information Data mining techniques are needed by using the FP-Growth algorithm. The application of the FP-Growth algorithm to produce form association patterns violence. Hardness data is 420 data, the best 7 rules have been obtained with min value support 50% and min value support 60%. On the best rule results have given a recommendation (solution) so that the DP3AKB can handle the problem of violence well and on target.